Perencanaan Enterprise Architecture Menggunakan TOGAF ADM Pada Laboratorium Komputer Institut Bisnis Dan Informatika Stikom Surabaya - Setiawan, Dimas Arief; Sutomo, Erwin; Susilo, Tegar Heru (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
In Law No. 12 In 2012, Article 1 Paragraph 9 states that Tri Dharma College, hereinafter referred Tridharma is the obligation of universities to provide education, research, and community service. In his role as an institution of education and research activities, the Institute of Business and Information Stikom Surabaya through a Technical Implementation Unit (UPT) Computer Laboratory (Labkom) as a place for education and research development. The problem that occurs is the lack of planning and without thinking about a key element in the process of development of information systems at Labkom. The solution offered is to develop a blueprint design (blueprint) enterprise architecture using the TOGAF ADM to assist the parties Labkom Stikom Surabaya as a reference in aligning business processes that exist in the infrastructure / IT needed as a support. The research proves that through the parent document enterprise architecture planning can produce a draft infrastructure / IT dibutukan Labkom Stikom Surabaya to assist in the development of services / IT as supporting the business processes of academic